A Study of Known Vulnerabilities and Exploit Patterns in Blockchain Smart Contracts - Astriratma, Ria (Bright Institute, 2025)
Blockchain smart contracts are pivotal to decentralized applications, yet their security remains a critical challenge. This study analyzes a dataset of 1,000 smart contracts to investigate known vulnerabilities, audit practices, and exploit patterns. The results reveal that audited contracts are significantly less prone to exploitation, with 75% exhibiting no exploit history compared to 55% of non-audited contracts.